Evaluation of the need and potential of harmonizing methods for common vole abundance estimation and the diagnosis of infections with Francisella tularensis - A questionnaire survey - Sonnenburg, Jana; Gortázar, Christian (2015)
Resumen del póster presentado al APHAEA Consultation Workshop,celebrado en Utrecht el 18 de marzo de 2015.-- et al. [Background]: The APHAEA (harmonized Approaches in monitoring wildlife Population Health, and Ecology and Abundance, www.aphaea.org) project aims to establish a European wildlife disease surveillance network capable of providing reliable estimates on abundance of wildlife species and occurrence and distribution of pathogens in key wildlife species. For this purpose, the host-pathogen combination Common Vole (Microtus arvalis) and Francisella tularensis was selected. [Methods]: A questionnaire was designed to collect information on host abundance and pathogen occurrence from historical records, current studies or data which will be potentially accessible in the future. The questionnaire was circulated among the core project partners and voluntary external partners. [Results]: We received 17 completed questionnaires from 13 participating European countries. There is a substantial heterogeneity concerning the used data sources for estimating common vole abundance. Even if snap trapping was performed as proposed by APHAEA, different snap trapping protocols were used. Furthermore, the questionnaire showed that the population abundance estimation is mostly not accompanied by disease monitoring and surveillance; and that different protocols may be used for both purposes. [Conclusions]: Although heterogeneity could be shown, the intention to harmonize the used methods was clearly demonstrated by the participants. Crucial information regarding the used methods for abundance estimation as compared to the proposed harmonized methods was obtained. Peer reviewed